2018
DOI: 10.1103/physrevb.97.155124
|View full text |Cite
|
Sign up to set email alerts
|

Observation of valleylike edge states of sound at a momentum away from the high-symmetry points

Abstract: Topologically protected one-way transportation of sound, mimicking the topological properties of the condensed matter, has received greatly attentions. Thus far, the topological phases and the topological edge states of sound are yielded in the vicinity of the Dirac cones fixed at the high symmetric points of the Brillouin zone. Here, we present a new type of the phononic topological insulator in the square lattice with position-variational Dirac cones along the high symmetric lines. The emergence of such Dira… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 76 publications
2
27
0
Order By: Relevance
“…9). Similar to the earlier structure the edge states that arise are topologically nontrivial and gapless 22 .
Figure 9 C 4 v even-parity interfacial mode — Left and right columns, panels (a,b), pertain to the orange over blue and blue over orange stackings, respectively. Top panels show eigensolutions obtained from Fourier-Hermite method.
…”
Section: Resultssupporting
confidence: 67%
See 2 more Smart Citations
“…9). Similar to the earlier structure the edge states that arise are topologically nontrivial and gapless 22 .
Figure 9 C 4 v even-parity interfacial mode — Left and right columns, panels (a,b), pertain to the orange over blue and blue over orange stackings, respectively. Top panels show eigensolutions obtained from Fourier-Hermite method.
…”
Section: Resultssupporting
confidence: 67%
“…The parametric variation afforded to us, and encompassed in the variable , merely increases or decreases the slope thereby increasing or decreasing the distance between N and the Dirac point. Note that the Dirac cone occurs along the spatial symmetry path, σ h , of the structure due to the opposite parities of the bands; band repulsion occurs along the N path 22 thereby resulting in a partial band gap along N . If , then the partial gap along N isolates the Dirac cone along a portion of the IBZ path, NX .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerical studies that demonstrate the robustness of these topological states versus conventional designs for Newtonian systems are found in [50,[53][54][55]. Theoretical studies that demonstrate the existence of these modes under disorder are found in [56,57].…”
Section: D Dispersion Curves and Edge Statesmentioning
confidence: 84%
“…On the other hand, “topological acoustics” has attracted considerable attention over the past two years due to the fascinating quantum‐like effects in acoustic systems, which originates from studies of condensed‐matter states . Earlier pioneering approaches in the quest for constructing acoustic topological states in 2D systems relied on circulating fluid flows to mimic the quantum Hall effect, coupled resonator ring waveguides to mimic Floquet topological insulators, phononic “graphene” with double Dirac cones to mimic the quantum spin Hall effect and C 3v point symmetry phononic crystals composed of triangular rods, square lattices containing square inclusions to design a new class of valley‐Hall topological insulators (VHTI) . Furthermore, recently extensions into 3D were launched demonstrating the existence of Weyl points and Fermi arcs in topological acoustics …”
mentioning
confidence: 99%